The Impact of Principal Leadership and Committee Roles on Teacher Performance and Student Achievement - Alifatin Nur Faizah; Miftah Arifin; Moh Anwar; Achmad Mahrus Helmi (JUMPA : Jurnal Manajemen Pendidikan, 2025)
This study examines the influence of madrasah principals’ leadership and committee roles on teacher performance and their impact on student achievement in Madrasah Tsanawiyah (MTs) across Tabanan Regency, Bali Province. Employing a quantitative approach with an explanatory causal design, data were collected from 49 respondents selected through purposive sampling, including principals, teachers, and committee members with a minimum of two years of experience. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that all constructs meet validity and reliability criteria, with strong measurement and structural model performance (R² = 0.713 for teacher performance and 0.857 for student achievement; Q² = 0.9589). The findings reveal that principal leadership and committee roles have positive and significant effects on both teacher performance and student achievement. Among these, the committee role demonstrates the strongest influence, particularly in enhancing teacher performance. Teacher performance also significantly affects student achievement, confirming its role as a key mediating variable. Mediation analysis shows that teacher performance partially mediates the relationship between committee roles and student achievement, while it does not significantly mediate the effect of principal leadership. These findings highlight the importance of collaborative leadership and stakeholder involvement in improving educational outcomes. Practically, the study suggests that strengthening institutional leadership and community participation can effectively enhance teacher performance and student achievement in Islamic secondary education.